2019
DOI: 10.1016/j.fsi.2019.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the influence of surface proteins on the probiotic activity of Lactobacillus pentosus HC-2 in the Litopenaeus vannamei midgut via label-free quantitative proteomic analysis

Abstract: Our previously work showed that Lactobacillus pentosus HC-2 as probiotic could improve the growth performance, immune response, gut bacteria diversity and disease resistance of Litopenaeus vannamei. However, the probiotic mechanism of was not fully characterized. In the present study, histology and proteomic analysis was performed to explore the influence of HC-2 surface protein on its probiotic effects to L. vannamei after feeding the intact surface proteins or the probiotic treated with lithium chloride (LiC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
(40 reference statements)
2
13
0
Order By: Relevance
“…Our previous results showed similar facts (Yudiati et al 2016(Yudiati et al , 2019. The quantitative proteomic analysis and intestinal histology of L. pentosus probiotic activity were noted (Du et al 2019a). The surface proteins of L. pentosus signi cantly in uenced the protein transcription in the shrimp gut.…”
Section: Discussionsupporting
confidence: 76%
“…Our previous results showed similar facts (Yudiati et al 2016(Yudiati et al , 2019. The quantitative proteomic analysis and intestinal histology of L. pentosus probiotic activity were noted (Du et al 2019a). The surface proteins of L. pentosus signi cantly in uenced the protein transcription in the shrimp gut.…”
Section: Discussionsupporting
confidence: 76%
“…5.6 mm size in 1 h/individu. The most e cient digestive tract are individuals larger than 5.6 mmDu et al (2019a) was strengthened our results. LAB predominantly convinced metabolic and cell to cell signaling-related protein upregulation.…”
supporting
confidence: 84%
“…In some studies, cell‐free extract or fermentation supernatant of Lactobacillus plantarum was also found to be beneficial to the host (Zheng et al, 2017, 2020). Additionally, Lactobacillus pentosus HC‐2 treated with lithium chloride (LiCl) to eliminate non‐covalently bound surface proteins has an effect on probiotic actions in the shrimp midgut (Du et al, 2019). However, our study found that L .…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, cell-free extract or fermentation supernatant of Lactobacillus plantarum was also found to be beneficial to the host (Zheng et al, , 2020. Additionally, Lactobacillus pentosus HC-2 treated with lithium chloride (LiCl) to eliminate non-covalently bound surface proteins has an effect on probiotic actions in the shrimp midgut (Du et al, 2019). However, our study found that L. vannamei fed with live E. faecalis F7 preparation diets performed better in terms of weight gain rate (WGR), specific growth rate (SGR) and feed conversion ratio (FCR) when compared to that fed with a regular diet, dead bacteria, cell-free extract of E. faecalis F7 and E. faecalis F7 treated with LiCl (Figure 1).…”
Section: Discussionmentioning
confidence: 99%